Pengaruh TIKTOK Terhadap Pengetahuan dan Sikap Konsumsi Buah Dan Sayur Siswa SDN Karawang Wetan 1 - Fahmi Farizzi Shiddiq; Ratih Kurniasari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Consumption of Fruits and Vegetables which are a source of vitamins and minerals can optimize growth and development in children. The low consumption of fruits and vegetables in children can be caused by a lack of education on knowledge about fruits and vegetables for children. This research is a pre-experimental research with one-group pre-test post-test design. This research was conducted for three days which took place online at SDN Karawang Wetan 1, Karawang Regency on April 20 - April 23, 2021 using the gform application. This study aims to determine the differences and effects of the Tiktok video as a learning medium on the knowledge and attitudes of students' fruit and vegetable consumption at SDN Karawang Wetan 1. There are differences in knowledge and attitudes of fruit and vegetable consumption among students of SDN Karawang Wetan 1 after giving TIKTOK video learning media. There is an effect of providing TIKTOK video learning media on the knowledge and attitudes of fruit and vegetable consumption among SDN Karawang Wetan 1 students after.